AN ANALYSIS OF PREPOSITIONAL PHRASES FOUND IN FOLKATIVE INSTAGRAM ACCOUNT - Duha, Imanuel Hendrik; Yusmalinda, Yusmalinda; Nazara, Wa`ozisokhi (STBA Prayoga Padang, 2023)
Abstract This article aims to analyze the functions of prepositional phrases found in Folkative’s Instagram account. This research was qualitative research. The data were taken from Folkative’s Instagram account by taking screenshots of the posts on July 2022. The data were analyzed based on the functions of prepositional phrases proposed by Quirk, et al theory (1985). The writer found three main functions of prepositional phrases in Folkative’s Instagram Account. However, for the adverbial function, there are only adjunct and conjunct that are found. Moreover, the prepositional phrases which functions as post modifier of a noun are highly used in Folkative’s Instagram account.